Comparative evaluation of Nested RT-PCR and TaqMan real time PCR for ante mortem diagnosis of rabies from body secretion/excretion of animals - DANDALE, M; SINGH, C K; SANDHU, B S; DEKA, D; RAMNEEK, RAMNEEK; BANSAL, KARAN; SOOD, N K (The Indian Journal of Animal Sciences, 2013)
Nested RT-PCR and TaqMan real time PCR techniques were compared for rabies diagnosis in 62 biological fluid samples collected ante mortem from animals clinically suspected to be rabid. The average sensitivity of Nested RT-PCR technique obtained from fluid samples was detected as 61.68% while for TaqMan real time PCR it was 72.07%. Usage of molecular approaches for ante mortem rabies diagnosis from fluid samples lead to conclusion that body secretion (saliva, milk) and excretion (urine) can be a viable, alternative tool for the ante mortem diagnosis of rabies where standard sample collection is not feasible in aggressive rabid animals.